Endothelial cell adhesion molecules in meningococcal disease. Issue 1 (1st January 1999) - Baines, P B; Marzouk, O; Thomson, A P J; Sills, J A; Riordan, F A I; Hart, C A
Abstract : BACKGROUND: Endothelial damage is important in meningococcal disease. Cell adhesion molecules, including P selectin, E selectin, and intercellular cell adhesion molecule 1 (ICAM-1), are expressed by activated endothelium and then subsequently shed. METHODS: ICAM-1, P selectin, and E selectin were measured on admission to hospital in children with meningococcal infections. RESULTS: Concentrations of shed cell adhesion molecules are reported for 78 children. Eleven did not have meningococcal disease. Of the 67 with meningococcal disease, 40 had mild disease (Glasgow meningococcal septicaemia prognostic score (GMSPS) < 8) and 27 had severe disease (GMSPS ⩾ 8). E selectin and ICAM-1 values were higher in those with meningococcal disease. The E selectin values in those with severe disease were higher than in those with mild disease. P selectin concentrations were not altered in meningococcal disease, but those who died had lower concentrations. CONCLUSIONS: Endothelial activation in meningococcal disease is reflected by shed ICAM-1 and E selectin concentrations.